Using translation process research to explore the creation of subtitles: an eye tracking study comparing professional and trainee subtitlers - David Orrego-Carmona; Łukasz Dutka; Agnieszka Szarkowska (JoSTrans: The Journal of Specialised Translation)
Although translation process research (TPR) has become one of the most active fields in Translation Studies in the last 20 years, the process of subtitle creation has received little attention. This subtitling process research study adopts TPR methods to explore the production of interlingual subtitles. We conducted two experiments: Experiment 1 comparing professional subtitlers and subtitling trainees using the same subtitling tool, and Experiment 2 comparing two groups of professional subtitlers, each using a different subtitling programme. We collected data from eye tracking, screen recording, mouse clicks and keystroke logging, and post-experiment interviews. In Experiment 1, professionals and trainees exhibited different subtitling processes, with trainees following a highly structured sequence of viewing, spotting, translation and revision stages. Professionals were slightly faster, but text condensation levels were similar for both groups. In Experiment 2, the options offered by the subtitling tool significantly affected the process. Additionally, the age and experience were suggested as relevant factors influencing the task. Our findings confirm the suitability of using TPR methods to study the production of subtitles and set the grounds for further studies in the field of subtitling process research.